Theoretical and experimental investigation on the effect of supply pressure on the nonlinear behaviors of the aerostatic bearing-rotor system. (September 2021) - Zhang, Jianbo; Han, Dongjiang; Song, Mingbo; Xie, Zhongliang; Rao, Zhushi; Zou, Donglin
Highlights: The effect of supply pressure on the nonlinear behaviors is studied theoretically and experimentally. The numerical and experimental results reveal complex nonlinear behaviors. The rotational speed of the sub-synchronous vibration can be enhanced by increasing supply pressure. The subsynchronous vibration can be retrained and even eliminated by increasing the supply pressure further. A simple and convenient method based on adjustment of supply pressure is proposed to restrain the subsynchronous vibration. Abstract: With low friction, high rotational speed and low motion error, the aerostatic bearings have been widely applied to the high speed rotating and high precision machines. However, comparison with liquid-lubricated bearings, the gas lubrication is compressible and has low viscosity and then the aerostatic bearings tend to generate self-excited vibration phenomenon which results in the instability and then limits future improving of the precision and rotational speed. So, it is necessary to study the nonlinear behaviors of the aerostatic bearing-rotor system. In this paper, based on the bifurcation diagram, orbit of rotor center, frequency spectrum diagram, Poincaré map and speed waterfall diagram, the effects of supply pressure and rotational speed on the nonlinear behaviors of the aerostatic bearing-rotor system are studied theoretically and experimentally. The results show that there exists complex nonlinear behaviors and the nonlinear behaviors are delayed to generate by improving supply pressure. According to the results, a simple and convenient method based on adjustment of supply pressure is proposed to restrain and even eliminate the subsynchronous vibration and the experimental results verify the correctness and feasibility of the method.